An Analysed Design Of Charger Automatic Battery Based On Thyristor - Hafiz Al Hakim Nasution; Zulkarnain Lubis; Beni Satria (Jurnal Scientia, 2024)
Lead-acid batteries (batteries) are one of the most widely used resource components. Starting from small capacity for motorbikes, uninterruptible power supplies (UPS), up to hundreds of amperes for industrial use. When used, this battery needs to be recharged after use to obtain a stable voltage and current. In the charging process there are many ways that can be done, from rectifiers without filters, using filters to automatic ones (can detect the battery voltage level and turn itself off if the battery is fully charged). Automatic Battery Charger (ABC) is an electronic device designed to charge batteries automatically with high efficiency. One of the key components in ABC is the thyristor, a power control semiconductor that allows fast and safe battery charging. This research aims to design and implement ABC using a thyristor as a switch to control battery charging current. The methods used in this research include analyzing system requirements, designing electronic circuit schemes, selecting appropriate components, making and testing prototypes, and evaluating system performance. The designed ABC has features such as battery voltage detection to stop charging when the battery reaches full level, protection against overcurrent, and an LED indicator to display charging status. Test results show that ABC with thyristors can charge batteries with high efficiency and safely. The system is able to charge the battery quickly without producing excess heat which can damage the battery. In addition, this ABC is also equipped with security features that ensure safe and reliable operation. This research contributes to the development of more efficient and environmentally friendly battery charging technology. Implementing ABC with a thyristor as a battery charging current control switch can be an effective and energy-saving solution for automatic battery charging.